Recent Developments and Applications of Ionic Liquids in Gas Separation Membranes - Zia ul Mustafa, M. (Wiley-VCH Verlag, 2019)
Flue gas emissions and the harmful effects of these gases urge to separate and capture these unwanted gases. Ionic liquids due to negligible vapor pressure, thermal stability, and wide electrochemical stability have expanded its application in gas separations. A comprehensive overview of the recent developments and applications of ionic liquid membranes (ILMs) for gas separation is given. The three general classifications of ILMs, such as supported ionic liquid membranes (SILMs), ionic liquid polymeric membranes (ILPMs), and ionic liquid mixed-matrix membranes (ILMMMs) along with their applications, for the separation of various mixed gases systems is discussed in detail. Furthermore, issues, challenges, computational study, and future perspectives for ILMs are also considered. Â© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim